Understanding metastasis mixed-treatment responses through genomic analyses - Susana Garcia-Recio; Paola Zagami; Brooke M. Felsheim; Amy Wheless; Kerry Thomas; Renato Trimarchi; Lisa A. Carey; Charles M. Perou (npj Breast Cancer)
Abstract Early-stage and metastatic breast cancers (MBC) can exhibit genomic heterogeneity, even within the same individual. Response to therapy in metastatic breast cancer patients with multiple metastases can also be heterogeneous, with different degrees of responsiveness to the same drug(s) across metastatic sites, termed “mixed response,” within the same patient. Whether this treatment response variability is influenced by factors such as intrinsic tumor characteristics of metastatic lesions and/or the microenvironment is unknown. Through genomic analysis of multiple metastases from the same patient, assayed in 6 different patients who had exhibited mixed response on imaging, we identified that higher regulatory T cells (T reg) and CDKN2A gene expression values correlate with non-response, while the KRAS gene, KRAS amplicon, and CD8T cells were associated with response in individual metastases. These genomic features may explain mixed clinical responses and provide valuable insights into intrapatient variations in treatment sensitivity.